Brief and long co-incubation of sperm and oocytes for in vitro fertilization: a meta-analysis of randomized controlled trials - Yiyue Fan; Zeyu Wu; Fang Peng; Hongyao Peng; Xin Liang; Shaomi Zhu (BMC, 2023)
Abstract Background There is still no consensus on the optimal time of oocyte-sperm co-incubation during in vitro fertilization and embryo transfer (IVF-ET). The aim of this meta-analysis was to compare the effects of brief (1-6 h) and long (16-24 h) gametes co-incubation time on IVF outcomes. Methods The study protocol was registered online through PROSPERO (CRD42022337503) and PRISMA guidelines were followed in the present study. The following databases were searched from inception to May 2022 for randomized controlled trials (RCTs): PubMed, Embase, Cochrane library, Web of Science, using search terms related to IVF, gametes, time of co-incubation and reproductive outcome measure. Studies comparing outcomes of brief co-incubation to that of long co-incubation during IVF, and reporting primary outcome (live birth rate), secondary outcomes (clinical pregnancy rate; ongoing pregnancy rate; miscarriage rate; normal fertilization rate; polyspermy rate; top-quality embryo rate; implantation rate) were searched. A total of 11 studies were included in the meta-analysis. Combined odds ratio (OR) and 95% confidence interval (CI) were calculated for the data. Statistical heterogeneity analysis between studies was assessed by Cochran Q and I2 statistic with a significant threshold of P < 0.05. Methodologic quality assessment of RCTs was made for potential risk of bias with Cochrane Risk of Bias Tool. Results Compared to long-term co-incubation, brief co-incubation had an advantage in increasing implantation rate (OR: 1.97, 95% CI: 1.52-2.57), ongoing pregnancy rate (OR: 2.18, 95% CI: 1.44-3.29) and top-quality embryo rate (OR: 1.17, 95% CI: 1.02-1.35). However, brief co-incubation of gametes had no advantages in the live-birth rate (OR: 1.09, 95% CI: 0.72-1.65), miscarriage rate (OR: 1.32, 95% CI: 0.55-3.18), clinical pregnancy rate (OR: 1.36, 95% CI: 0.99-1.87) and polyspermy rate (OR: 0.80, 95% CI: 0.48-1.33) than long-term co-incubation. Additionally, the brief co-incubation was associated with lower normal fertilization rate (OR: 0.89, 95% CI: 0.80-0.99), compared with long co-incubation. Conclusions Brief co-incubation of gametes had the advantages in increasing implantation rate, ongoing pregnancy rate and top-quality embryo rate than long-term co-incubation. However, the live-birth rate displayed no difference between the two in vitro fertilization methods. Gametes co-incubation time should be individualized according to each patient's IVF history, infertility causes and the semen parameters.